Relationships Between Cultural Intelligence, Personality, Cross-Cultural Adjustment and Job Performance Amongst Expatriates in Malaysia - Sri Ramalu, Subramaniam (2010)
Many studies have been conducted by researchers either academia or practitioner to understand factors contributing to expatriate effectiveness in the international assignments. However, the absence of reliable individual factors contributing to expatriate effectiveness in international assignments has remained the gap in the literature. The present study fills the gap by examining the relationship between individual differences consist of cultural intelligence and personality and expatriate effectiveness in terms of cross-cultural adjustment and job performance using a sample of 332 expatriates working in Malaysia. Sample list of the study drawn from 24 directories of foreign Business Chamber of Commerce in Malaysia. Data was collected using the survey method consist of mail and online questionnaire. The nine research questions and eight research objectives of the study answered by performing appropriate descriptive and inferential statistical analyses. The eight main hypotheses of the study tested using the hierarchical and multiple regression analyses. The findings of the study revealed that there is a significant positive relationship between (i) cultural intelligence and cross-cultural adjustment; (ii) cultural intelligence and job performance; (iii) personality and cultural intelligence; (iv) personality and cross-cultural adjustment; (v) personality and job performance; and (vi) cross-cultural adjustment and job performance. In this study, motivational and behavioural dimension of cultural intelligence and personality factors of agreeableness, openness to experience and conscientiousness found to be positively related to most of the dimensions of cross-cultural adjustment and job performance. The findings imply that the motivational and behavioural dimension of cultural intelligence and personality factors of agreeableness, openness to experience and conscientiousness are more significant in predicting cross-cultural adjustment and job performance among expatriates in Malaysia. Findings of this study also revealed that cross-cultural adjustment mediates the relationship between individual differences and job performance, implying that cultural intelligence and personality explains the variance in job performance indirectly, mediated through cross-cultural adjustment. The mediating role played by cross-cultural adjustment helps to explain the underlying process that is responsible for the relationship between individual differences and job performance of expatriates. The findings of this study have significantly contributed to the advancement of knowledge in cross-cultural management field evident that cultural intelligence and personality factors are vital cross-cultural competency that facilitates expatriates cross-cultural adjustment and job performance in international assignments. With the evidence on the usefulness of cultural intelligence and personality factor to facilitate expatriate cross-cultural adjustment and job performance, the findings of this study also have practical implications to the expatriating firms in the area of selection, training and development of candidate for international assignments.